2014
DOI: 10.1037/cns0000014
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis and cognition.

Abstract: This article summarizes the contributions of hypnosis to our understanding of cognition. These contributions have been especially salient in the study of memory, and include source amnesia and the distinction between episodic and semantic memory; the occurrence of semantic priming in implicit (unconscious) memory; and paramnesia (false memory). Posthypnotic amnesia shows that explicit and implicit memory can be dissociated even under optimal encoding conditions. The hypnotic alterations of perception may expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 120 publications
0
17
0
Order By: Relevance
“…Finally, it should be mentioned that our results could arguably limit the possibilities of implementing hypnosis as a classic subliminal masking tool, as purported by some theoretical reviews in the field ( Kihlstrom 2014 ; Landry et al . 2014 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, it should be mentioned that our results could arguably limit the possibilities of implementing hypnosis as a classic subliminal masking tool, as purported by some theoretical reviews in the field ( Kihlstrom 2014 ; Landry et al . 2014 ).…”
Section: Discussionmentioning
confidence: 84%
“…Much has been written about the promising venues of hypnosis as a tool for cognitive research ( Oakley and Halligan 2009 , 2013 ; Raz 2011 ). In particular, recent reviews have proposed that hypnotic negative and positive hallucinations would be a valuable asset for the study of consciousness ( Kihlstrom 2014 ; Landry et al . 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This type of experimental research, designated intrinsic (Cox & Bryant, 2008; Wagstaff, 1996), asks, for example, whether hypnotic-suggestibility is related to the capability of concentration, fantasy, or daydreaming (for review, see Lynn et al, 2019). (2) Do (posy)hypnotic suggestions affect perception or performance in specific tasks, such as those measuring cognitive functions (for review, see Kihlstrom, 2013; Kihlstrom, 2014)? Such studies, sometimes referred to as instrumental (Cox & Bryant, 2008; Wagstaff, 1996), ask, for instance, whether (post)hypnotic suggestions can subdue pain perception (e.g., Perri et al, 2019) or facilitate inhibition of irrelevant but intrusive information (e.g., Zahedi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical hypnosis can evoke profound changes in a series of cognitive and metacognitive mechanisms both during and after hypnosis. Hypnosis research has also shed light on cognitive phenomena that might otherwise go unnoticed [12,15].…”
Section: The Role Of Clinical Hypnosis In Metacognitive Knowledgementioning
confidence: 99%
“…Lindeløv et al [17], using a randomized controlled trial found that hypnotic suggestions can actively restore working memory performance in patients with acquired brain injury. Kihlstrom's et al [15] pointed out that hypnosis can dissociate different forms of memory such as those of episodic and semantic memory allowing them to operate independently and accordingly with the therapeutic purposes. In addition, it facilitates memory accessibility and recall.…”
Section: The Role Of Clinical Hypnosis In Metacognitive Knowledgementioning
confidence: 99%